1998
DOI: 10.1074/jbc.273.17.10665
|View full text |Cite
|
Sign up to set email alerts
|

Identity of the Residues Responsible for the Species-restricted Complement Inhibitory Function of Human CD59

Abstract: The membrane-anchored glycoprotein CD59 inhibits assembly of the C5b-9 membrane attack complex (MAC) of human complement. This inhibitory function of CD59 is markedly selective for MAC assembled from human complement components C8 and C9, and CD59 shows little inhibitory function toward MAC assembled from rabbit and many other non-primate species. We have used this species selectivity of CD59 to identify the residues regulating its complement inhibitory function: cDNA of rabbit CD59 was cloned and used to expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 44 publications
5
29
0
Order By: Relevance
“…However, 50% of NHL patients are unresponsive to rituximab or resistant after therapy. 25 Extensive evidence indicates that the high expression of mCRPs on the cancer cells influences the efficacy of the rituximab-mediated CDC effect. 39 Consistently, we also demonstrated that the high level of CD59 expression was the major cause of lymphoma resistance to rituximab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 50% of NHL patients are unresponsive to rituximab or resistant after therapy. 25 Extensive evidence indicates that the high expression of mCRPs on the cancer cells influences the efficacy of the rituximab-mediated CDC effect. 39 Consistently, we also demonstrated that the high level of CD59 expression was the major cause of lymphoma resistance to rituximab.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,[25][26][27][28][29] Recently, we developed a novel, potent, non-toxic and specific antihCD59 inhibitor: the domain 4 of intermedilysin (ILY). This inhibitor is defined as rILYd4.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, plasmids encoding cd59b and cd59a proteins containing a FLAG peptide tag (DYKDDDDK) were constructed to help visualize surface expression of the proteins by indirect immunofluorescence using a FLAG-specific Ab. A similar approach involving N-terminal peptide tagging has been successfully used in previous functional studies of human CD59 (26,27). The FLAG sequence (encoded by a 24-nucleotide sequence GACTACAAGGACGACGATGACAAG) was inserted into the coding region of cd59b or cd59a (after the second amino acid (lysine) in the predicted mature cd59b protein, or after the second amino acid (threonine) in the mature cd59a protein) to yield Nterminal tagged cd59 proteins after cleavage of the signal peptides.…”
Section: Construction Of Cd59b and Cd59a Expression Plasmidsmentioning
confidence: 99%
“…Human homologues were first recognized with the identification of CD59, which has a well characterized role as an inhibitor of the complement membrane attack complex (11)(12)(13). Certainly, CD59 homologues have been characterized in rabbit (14), rat (15), pig (16), and mouse (17). At the present time human homologues for several mouse Ly-6SF members are known, including ThB (18), Ly-6H (19), and TSA-1/Sca-2/RIG-E (20,21).…”
mentioning
confidence: 99%